Role of Endoscopic Ultrasonography in Guiding Treatment Plans for Upper Gastrointestinal Subepithelial Tumors - Jeong Seop Moon (Korean Society of Gastrointestinal Endoscopy, 2016)
Gastrointestinal (GI) subepithelial tumors (SETs) are usually observed incidentally by endoscopy and have diverse prognoses, varying from benign to potentially malignant. When a GI SET is suspected, endoscopic ultrasonography (EUS) is the most accurate diagnostic method to differentiate it from extraluminal compression. To determine the nature of GI SETs, EUS is also the most accurate diagnostic method, and reveals the precise sonographic nature of the lesion. There are some SETs with typical EUS findings of GI SETs, but most hypoechoic lesions are difficult to diagnose based on EUS images alone. EUS is also helpful to determine GI wall involvement in SETs and optimal treatment methods. For the diagnosis of GI SETs, obtaining a proper specimen is essential. EUS-guided cytology or biopsy methods such as fine-needle aspiration, Tru-Cut biopsy, and the newly introduced fine-needle biopsy (FNB) provide good results. To increase the diagnostic yield for GI SETs, cytology with immunocytochemical staining is used for cytological interpretation, resulting in good diagnostic yields. Recently, EUS-FNB using cheese slicer technology has been introduced, and has been reported to provide good diagnostic results for GI SETs.